The Islamic Personality and It’s Attribute to Social Psychological Theory - Nuriman Nuriman; Aswati Bt. Hamzah; Yusnaini Yusnaini; Yuliza Yuliza (Master Program of Sociology, Universitas Malikussaleh,, 2023)
Personality is a topic that has been widely discussed in the scientific world through the widespread works of great philosophers. Many works of literature have studied the Islamic character to find scientific premises regarding personality formation. This study aimed to explain the importance of connecting the concept of Islamic personality with aspects of emotion, motivation, and attitude. In particular, the attitude aspect in the Islamic context is divided into inter-social and pro-social attitudes. Through an in-depth analysis that combines the perspectives of Islamic scholars, sociological, and psychological theories, this study resulted in an understanding of the relationship between religion and spirituality with emotions, motivation, inter-social, and pro-social attitudes. In the context of Islamic personality formation, Islam emphasizes that a person's personality is not only influenced by biological factors alone, but also by subjective values related to character formation. The implications of this paper provide detailed solutions and answer questions about the complex relationship between emotions, motivations, and attitudes with the formation of an Islamic personality. In the context of inter-social attitudes, Islam encourages individuals to develop attitudes that involve healthy and constructive social interactions with others. Additionally, in a pro-social attitude, Islam encourages individuals to prioritize attention and concern for the welfare of society as a whole.